Implementation of Pedagogical, Andragogical, and Heutagogical Approaches in Education System Sustainability - Mochamad Kamil Budiarto; Munawir Yusuf; Subagya (Universitas Pendidikan Ganesha, 2023)
Nowadays it is very important for educators to know a theme regarding approaches to learning. Therefore, this study aims to analyze various learning approaches such as pedagogic, andragogic, and heutagogic as learning approaches that are commonly used in education delivery. The research method used is a literature review. The data collection technique for this research was to study articles related to pedagogic, andragogic, and heutagogic followed by analysis of qualitative descriptive data with a sample number after going through the screening and feasibility stages of 14 papers, total of 459 papers found from three databases during the identification process. The results of this study indicate that each approach has different characteristics and can be applied according to the characteristics of the students and the material, the pedagogic approach can be applied at the early education level, andragogic is very suitable for adult learning, and the heutagogic approach. This approach is relevant to higher education. Through this research can be used as a reference for teachers to choose an approach that suits the characteristics of their students.